Dynamic modelling and simulation of rail car suspension systems using classic controls. Issue 1 (1st January 2019) - Daniyan, I. A.; Mpofu, K.; Daniyan, O. L.; Adeodu, A. O.
Abstract: Classic and advance control systems usually designed to improve the performance rail car suspension systems. In this study, the dynamic modelling and simulation of classic control for rail car suspension systems was carried out. Using nine degrees of freedom, the modelling process comprises of the representation of the rail car system with a schematic of the rail car body, its suspension system and rail track followed by the generation of equations of motion. The represented rail car system was simulated in the MATLAB-Simulink 2017a environment based on the equations of motion generated. Also, the proportional, integral and derivative (PID) control was employed to control the rate of disturbances based on the Ziegler-Nichols tuning rules. The results obtained indicate that the amplitude of oscillations, bandwidth and phase margin are key parameters that influences the stability of the rail car during movement. Also, the introduction of the PID control brought about significant reduction in the amplitude of oscillation, vibration, noise, rise time as well as rejection of disturbances and elimination of the steady-state error thereby increasing the stability and ride comfort of the rail car.